2016
DOI: 10.1186/s13256-016-0923-6
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment of an unerupted mandibular canine tooth in a patient with mixed dentition: a case report

Abstract: BackgroundThe aim of this case report was to describe the surgical–orthodontic treatment of an unerupted mandibular canine tooth in a 9-year-old girl.Case presentationA 9-year-old white girl presented with an unerupted right mandibular canine tooth. Combined surgical–orthodontic treatment was performed to correct dental impaction and to achieve good aesthetic and functional results.ConclusionOrthodontic treatment achieved all of the required objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…While in the present study a significant decrease in crowding was observed after treatment with SA, there are no previous data in the literature about the changes of lower dental arch dimensions after a treatment with this appliance. Looking at the present results, SA seems to be more effective with respect to the LB in achieving a higher increase in the intercanine dimension, with possible clinical implications in the prevention of the lower canine impaction [28,29].…”
Section: Discussionmentioning
confidence: 54%
“…While in the present study a significant decrease in crowding was observed after treatment with SA, there are no previous data in the literature about the changes of lower dental arch dimensions after a treatment with this appliance. Looking at the present results, SA seems to be more effective with respect to the LB in achieving a higher increase in the intercanine dimension, with possible clinical implications in the prevention of the lower canine impaction [28,29].…”
Section: Discussionmentioning
confidence: 54%
“…About 4% of patients referred to orthodontists are affected by this condition, and the ratio is 4:1 for palatally vs buccally impacted canines (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…A tooth is considered “impacted” when it fails to erupt in the oral cavity within the expected developmental window. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Most frequently impacted teeth are the third molars (20%–30%) because they are the last teeth to erupt in the oral cavity, after that maxillary canines with palatal dislocation, mandibular second premolars (0.3%), and maxillary central incisors (0.1%). [ 2 8 9 ]…”
Section: Introductionmentioning
confidence: 99%